Literature review on the use of Artificial Intelligence focused on visual impairment care - Alvarado-Salazar, Ruth (2022)
This paper performs a systematic literature review focused on the attention to visual impairment supported by artificial intelligence categorizing the relevance of contributions on machine learning. The main objective is to determine techniques that are applied for the attention to visual impairment using artificial intelligence during the years 2017 to 2021 from different relevant studies found in indexed bases such as Scopus, Web of Science, IEEExplore and Springer. From a total of 545 publications, 33 articles categorized in four areas, machine learning, artificial neural networks, natural language processing and artificial vision related to the field of visual impairment were determined. There is evidence of application trends with techniques that involve artificial intelligence and that allow opening fields where technology has a challenge that to some extent is a support to people with low vision and propose mechanisms to improve the quality of life.